HOW TO BUILD SERIOUS GAMES. - Kelly, Henry; Howell, Kay; Glinert, Eitan; Holding, Loring; Swain, Chris; Burrowbridge, Adam; Roper, Michelle (Communications of the ACM, 2007)
The article discusses how computer programmers can build serious games that provide education for their users. The computer game Immune Attack, which requires players to learn the rules of the immune system to advance, is examined. The game, which is sponsored by the National Science Foundation, combines a realistic 3D depiction of biological structure and function with educational technologies to teach immunology to high school and college freshmen. The authors examine the game design and integration with learning.